The Effects of Calcium Supplementation and Exercise on Bone Density in Elderly Chinese Women - Lau, E. M. C. (Institutional Knowledge at Singapore Management University, 1992)
A randomized controlled trial was carried out to determine whether calcium supplementation and load-bearing exercise can increase or maintain bone mass in the elderly. Fifty Chinese women, aged 62–92 years, living in a hostel for the elderly in Hong Kong were randomized to enter one of four treatment groups: (I) calcium supplementation of 800 mg (as calcium lactate gluconate) daily; (II) load-bearing exercise four times a week plus a daily placebo tablet; (III) calcium supplementation daily and load-bearing exercise four times a week; (IV) a placebo tablet daily. The interventions went on for 10 months. The bone mineral density (BMD) was measured at three sites in the hip (femoral neck, Ward's triangle and intertrochanteric area) and the L2–4 level of the spine. The percentage change in BMD in 10 months was used as the main outcome measurement. The parathyroid hormone level and indices of bone metabolism were also measured before and after 10 months of intervention.